1971
DOI: 10.1126/science.173.4003.1237
|View full text |Cite
|
Sign up to set email alerts
|

Xenon as a Nucleophile in Gas-Phase Displacement Reactions: Formation of the Methyl Xenonium Ion

Abstract: Xenon undergoes reaction with protonated methyl fluoride in the gas phase to form abundant quantities of the stable methyl xenonium ion, CH(3)Xe(+). Estimated values for the xenon-carbon and krypton-carbon bond strengths in the rare gas-methyl molecular ions are 43 +/- 8 and 21 +/- 15 kilocalories per mole, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 24 publications
(20 reference statements)
2
10
0
Order By: Relevance
“…Equation 2describes the nucleophilic displacement of HF from the F-protonated isomer of NF 3 by Xe. A process like this was first reported by Holtz and Beauchamp, 267 who observed Reaction (3) H 3 C-FH + + Xe ® H 3 C-Xe +…”
Section: +supporting
confidence: 61%
“…Equation 2describes the nucleophilic displacement of HF from the F-protonated isomer of NF 3 by Xe. A process like this was first reported by Holtz and Beauchamp, 267 who observed Reaction (3) H 3 C-FH + + Xe ® H 3 C-Xe +…”
Section: +supporting
confidence: 61%
“…The reactions of NF 3 H + with noble gases have not yet been investigated. It was, however, reported previously [48] that gaseous protonated CH 3 F reacts with Xe to form H 3 CXe + and HF. One of us subsequently observed that SiF 4 H + reacts with Xe to form HF and F 3 SiÀXe + , [37] and, quite recently, we noticed the formation of F 3 GeÀXe + by the reaction between GeF 4 H + and Xe.…”
Section: Resultsmentioning
confidence: 84%
“…In the crystals of the dark green compound, weak multiple contacts exist between xenon and fluorine atoms. 1063,1065 Even methylated xenon and krypton, CH 3 Xe þ and CH 3 Kr þ , have been observed by Holtz and Beauchamp 1066 in the gas phase. 1051 Of the possible cationic species (Xe n mþ , n ¼ 2-4; m ¼ 1, 2), calculated vibrational spectra and energies agree well with those observed for Xe 4 þ , but the presence of higher xenon aggregates (Xe 4 þ ÁXe n ) cannot be ruled out.…”
Section: Hmentioning
confidence: 85%